First-principles investigation of the Schottky contact for the two-dimensional MoS2 and graphene heterostructure. Issue 65 (23rd June 2016) - Liu, Biao; Wu, Li-Juan; Zhao, Yu-Qing; Wang, Ling-Zhi; Cai, Meng-Qiu
Abstract : The electronic properties of an MoS2 and graphene heterostructure are investigated by density functional calculations. Abstract : The electronic properties of an MoS2 and graphene heterostructure are investigated by density functional calculations. Our results show that both the intrinsic properties of MoS2 and graphene at the equilibrium interfacial distance are preserved in the weak van der Waals contact. Furthermore, Schottky doping for the MoS2 and graphene contact can be tuned by the interfacial distance. Our calculations show that the Schottky doping can be transformed from an n-type Schottky contact to a p-type Schottky contact when the interfacial distance decreased. We find that interfacial charge transfer and the Fermi level shift determines the Schottky barrier transition from an n-type Schottky contact to a p-type Schottky contact. Our studies may prove to be instrumental in the future design and fabrication of van der Waals based field effect transistors.